Damage localization in aluminum plate with compact rectangular phased piezoelectric transducer array - Liu, Zenghua; Sun, Kunming; Song, Guorong; He, Cunfu; Wu, Bin (Mechanical systems and signal processing, 2016)
In this work, a detection method for the damage in plate-like structure with a compact rectangular phased piezoelectric transducer array of 16 piezoelectric elements was presented. This compact array can not only detect and locate a single defect (through hole) in plate, but also identify multi-defects (through holes and surface defect simulated by an iron pillar glued to the plate). The experiments proved that the compact rectangular phased transducer array could detect the full range of plate structures and implement multiple-defect detection simultaneously. The processing algorithm proposed in this paper contains two parts: signal filtering and damage imaging. The former part was used to remove noise from signals. Continuous wavelet transform was applicable to signal filtering. Continuous wavelet transform can provide a plot of wavelet coefficients and the signal with narrow frequency band can be easily extracted from the plot. The latter part of processing algorithm was to implement damage detection and localization. In order to accurately locate defects and improve the imaging quality, two images were obtained from amplitude and phase information. One image was obtained with the Total Focusing Method (TFM) and another phase image was obtained with the Sign Coherence Factor (SCF). Furthermore, an image compounding technique for compact rectangular phased piezoelectric transducer array was proposed in this paper. With the proposed technique, the compounded image can be obtained by combining TFM image with SCF image, thus greatly improving the resolution and contrast of image. •The compact rectangular phased transducer array allows full-range damage detection.•Continuous wavelet analysis was applicable to signal filtering.•A compounding algorithm is proposed for the defect imaging.•The algorithm greatly improved the resolution and contrast of images.•The array can not only detect a single hole defect but also identify multi-type defects.